Impact of centralized evaluation of bone marrow histology in systemic mastocytosis - Jawhar, Mohamad; Schwaab, Juliana; Naumann, Nicole; Fabarius, Alice; Hofmann, Wolf-Karsten; Metzgeroth, Georgia; Reiter, Andreas (European journal of clinical investigation, 2016)
Background Bone marrow (BM) histology/immunohistochemistry, KIT D816V mutation analysis and serum tryptase measurements are mandatory tools for diagnosis of systemic mastocytosis (SM). Materials and methods Within the ‘German Registry of Disorders on Eosinophils and Mast Cells’, we identified 65 patients with SM who had two consecutive BM biopsies. The first biopsy was evaluated by a local pathologist (LP) and the second biopsy by a reference pathologist (RP) of the ‘European Competence Network on Mastocytosis (ECNM)’. Results Final diagnoses by RP were SM (n = 27), SM or aggressive SM (ASM) with associated clonal haematological non-mast cell lineage disease [(A)SM-AHNMD, n = 34)] or mast cell leukaemia ± AHNMD (n = 4). In 15 of 65 patients (23%), initial diagnoses by LP were incorrect (by overlooking SM), for example primary myelofibrosis (n = 3), myelodysplastic/myeloproliferative neoplasm unclassified (n = 3) or B-cell lymphoma (n = 2). Fourteen of 15 patients (93%) with incorrect diagnosis had an advanced SM, mostly (A)SM-AHNMD. In the 50 concordantly diagnosed patients, immunohistochemical markers for quantitative assessment of mast cell infiltration, for example CD117 (KIT) or CD25, were applied by LP in only 34 of 50 patients (68%), and mutational analysis for KIT D816V was performed or recommended in only 13 of 50 patients (26%). Finally, the subclassification of SM was discordant because LP did not diagnose AHNMD in nine of 50 (18%) patients. Conclusions In summary, adequate diagnosis and subclassification of SM requires an in-depth evaluation of the BM by experienced haematopathologists (preferably in a reference centre) in combination with molecular genetics, serum tryptase level and clinical parameters.
Gesehen am 07.05.2019